Heterocyclic Synthesis of Some New Isoxazolidine Derivatives via 1,3-Dipolar Cycloaddition of Nitrones to Styrene - Qaddo, Akram Noori Mohammed; Abed, Amjed Ahmed (Iraqi Journal of Science, 2022)
A number of nitrones have been synthesized in three different procedures, starting with N-phenyl hydroxylamine, followed by the condensation reaction with some selected aldehydes. Furthermore, these nitrones were employed in the preparation of a number of new isoxazolidines. Cycloaddition reaction of nitrones to styrene produced the desired products.